The critical region thermodynamics of some statistical models - Soldatova, E.D.; Galdina, O.M. (Condensed Matter Physics, 2005)
We consider the exactly solvable Ashkin-Teller model and the hard square model, in which both scaling law hypothesis and the universality one are violated. The critical properties of these models have been investigated. The reasons for the violation of the scaling law and universality hypotheses are clarified.